2020
DOI: 10.1084/jem.20200288
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane TNF drives osteoproliferative joint inflammation reminiscent of human spondyloarthritis

Abstract: TNF plays a key role in immune-mediated inflammatory diseases including rheumatoid arthritis (RA) and spondyloarthritis (SpA). It remains incompletely understood how TNF can lead to different disease phenotypes such as destructive peripheral polysynovitis in RA versus axial and peripheral osteoproliferative inflammation in SpA. We observed a marked increase of transmembrane (tm) versus soluble (s) TNF in SpA versus RA together with a decrease in the enzymatic activity of ADAM17. In contrast with the destructiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 75 publications
6
44
0
Order By: Relevance
“…5b). Similar structures have been previously reported in human RA patients as well as in TNFdependent mouse models involving bone pathologies [22,23], with no evidence however of a critical contribution of bone marrow cells in the disease pathogenesis [22,24]. Gr1-positive neutrophils were found to accumulate mainly at the sites of the enthesis as well as loosely scattered in the bone marrow cavity and along the periosteum (Fig.…”
Section: New Bone Formation In Tmtnf Transgenic Mice Involves Mechanisupporting
confidence: 84%
“…5b). Similar structures have been previously reported in human RA patients as well as in TNFdependent mouse models involving bone pathologies [22,23], with no evidence however of a critical contribution of bone marrow cells in the disease pathogenesis [22,24]. Gr1-positive neutrophils were found to accumulate mainly at the sites of the enthesis as well as loosely scattered in the bone marrow cavity and along the periosteum (Fig.…”
Section: New Bone Formation In Tmtnf Transgenic Mice Involves Mechanisupporting
confidence: 84%
“…Biologically active TNF exists either in a secreted form or as a transmembrane (tm)-bound cytokine, the former being released upon cleavage of the latter by ADAM17 (A disintegrin and metalloproteinase 17, also known as TNF converting enzyme, TACE). In SpA, tmTNF appears to be more expressed in the synovial membrane than in rheumatoid arthritis, and this could be related to lower ADAM17 activity, raising the intriguing possibility that tmTNF could be specially involved in SpA [78]. Indeed, the TgA86 mouse that overexpresses tmTNF -due to defective ADAM17-develops axial and peripheral joint synovitis, enthesitis, and osteitis, with endochondral new bone formation ultimately leading to complete axial and peripheral joint ankylosis, typical of SpA [78,79].…”
Section: B-the Tmtnf-overexpressing Mousementioning
confidence: 99%
“…In SpA, tmTNF appears to be more expressed in the synovial membrane than in rheumatoid arthritis, and this could be related to lower ADAM17 activity, raising the intriguing possibility that tmTNF could be specially involved in SpA [78]. Indeed, the TgA86 mouse that overexpresses tmTNF -due to defective ADAM17-develops axial and peripheral joint synovitis, enthesitis, and osteitis, with endochondral new bone formation ultimately leading to complete axial and peripheral joint ankylosis, typical of SpA [78,79]. In this model, tmTNF expression by stromal cells appears critical, being required for peripheral arthritis and more pathogenic than tmTNF expressed by hematopoietic cells as for spondylitis.…”
Section: B-the Tmtnf-overexpressing Mousementioning
confidence: 99%
“…MiR-140 was shown to modulate the angiogenesis in hepatocellular carcinoma ( Hou et al, 2020 ). TNF is an important inflammatory factor and involved in inflammation response of multiple organs ( Liu R. et al, 2019 ; Kaaij et al, 2020 ). Our data suggested that deletion of TUG1 relieved LPS-induced hepatocyte inflammation and injury by regulating miR-140/TNF axis both in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%